2007
DOI: 10.3758/bf03194122
|View full text |Cite
|
Sign up to set email alerts
|

Nonword repetition in specific language impairment: More than a phonological short-term memory deficit

Abstract: The possible role of phonological short-term memory in the nonword repetition deficit of children with specific language impairment (SLI) was investigated in a study comparing serial recall and nonword repetition of sequences of auditorily presented CV syllables. The SLI group showed impairments in both serial recall and nonword repetition relative to typically developing children of the same age, however the SLI deficit in nonword repetition was greater and persisted even when differences on an independent me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
94
5
7

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(114 citation statements)
references
References 36 publications
8
94
5
7
Order By: Relevance
“…Similar results were obtained by Yuzawa et al (2011), who also found effects of temporal structuring of non-words on repetition performance, with stimuli containing a short interval in-between morae being easier to repeat than nointerval non-words. The opposite effect of intervals between syllables was described by Archibald and Gathercole (2007), where English-speaking children aged seven to thirteen years repeated non-words more accurately than sequences containing the same syllables with pauses in-between. Using a non-word repetition task controlling for stress, Roy and Chiat (2004) found that two-to four-year-olds, with English as a first language, rarely omitted stressed syllables.…”
Section: Word and Non-word Repetitionmentioning
confidence: 97%
See 1 more Smart Citation
“…Similar results were obtained by Yuzawa et al (2011), who also found effects of temporal structuring of non-words on repetition performance, with stimuli containing a short interval in-between morae being easier to repeat than nointerval non-words. The opposite effect of intervals between syllables was described by Archibald and Gathercole (2007), where English-speaking children aged seven to thirteen years repeated non-words more accurately than sequences containing the same syllables with pauses in-between. Using a non-word repetition task controlling for stress, Roy and Chiat (2004) found that two-to four-year-olds, with English as a first language, rarely omitted stressed syllables.…”
Section: Word and Non-word Repetitionmentioning
confidence: 97%
“…Prosodic features have been shown to affect typically developed children's nonword repetition ability in several languages (Archibald and Gathercole, 2007;Sahlén et al, 1999;Santos et al, 2006;Yuzawa and Saito, 2006;Yuzawa, Saito, Gathercole, Yuzawa and Sekiguchi, 2011). Yuzawa and Saito (2006) found that two-syllable nonwords pronounced with a high pitch accent facilitated repetition compared to non-words that were pronounced with a flat pitch accent, in Japanese children three to four, but not five to six, years of age.…”
Section: Word and Non-word Repetitionmentioning
confidence: 99%
“…Given the prevalence of motor coordination difficulties in children with LI (some estimates indicate up to ten times more likely, Hill, 1998;Iverson & Braddock, 2011), oromotor control may contribute even more to the NWR performance of children with language impairment than is the case in typically developing children (also see Archibald & Gathercole, 2007). In designing such assessments, a caveat to bear in mind is that previous studies have shown little to no relationship between language production skills and the ability to synthesize single oral movements, but rather a tighter relationship with the ability to combine and co-ordinate multiple oral movements (Alcock et al, 2000;Alcock & Krawczyk, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…These tests evaluate articulatory abilities and phonological short-term memory, which are variables that are considered independent from the environment. This shift has led to evolved diagnostic criteria (i.e., strictly applying language tests should be sufficient to establish a diagnosis) (8)(9)(10) .…”
Section: Introductionmentioning
confidence: 99%